Student attitudes towards anatomy teaching and learning in a multiprofessional context - Mitchell, B S; McCrorie, P; Sedgwick, P (Medical education, 2004)
Context  We carried out a survey of attitudes to learning anatomy amongst students from a range of health care disciplines in a multiprofessional context. Setting  A joint course called the Common Foundation Programme (CFP) presented by a hospital medical school and a joint university faculty of health and social care sciences in the UK in the first term of the students' courses. Participants  Students following degree courses in biomedical science, medicine, nursing, physiotherapy, diagnostic radiography and therapeutic radiography. Objectives  To assess student attitudes to cadaveric work, learning anatomy and multiprofessional learning, and to compare student performance between degree courses in an anatomy assessment. Design  A questionnaire was designed that requested demographic information and the students' attitudes to cadaveric work, anatomy learning and multiprofessional learning on a Likert scale. All students sat the same anatomy assessment at the end of the first term. Results  The biomedical science and medical students were the most apprehensive about entering the dissecting room. The biomedical science students enjoyed working in a multidisciplinary group the most. Assessment results varied widely and the physiotherapy and medical students scored more highly than students in other disciplines, although all students had participated in the same course. Conclusions  It was possible to teach anatomy in the context of the shared learning experience of the CFP, although performance varied widely. Reasons for the differences are discussed and suggestions for the design of multiprofessional courses involving anatomy are made.